The impact of Schistosoma blood fluke infection on the development of bladder cancer - Boszczyk, Piotr; Wrzesińska, Kinga (Journal of Education, Health and Sport, 2024)
Introduction and purpose Schistosomiasis is a significant health problem, particularly in countries in Africa. The disease is caused by blood flukes of the genus Schistosoma. There are five main species. Most infections are asymptomatic. Schistosomiasis can contribute to the development a lot of diseases. The aim of this article is to examine the impact of schistosomiasis on the human body, with particular focus on bladder cancer. Brief description of the state of knowledge Schistosoma are parasitic flatworms whose life cycle involves humans as the definitive host and freshwater snails as intermediate hosts. The cercarial larvae penetrate the human skin. Adult parasites lay eggs in the mucous membranes, causing inflammation and granulomatous reactions. Chronic schistosomiasis leads to tissue fibrosis, portal hypertension, squamous cell carcinoma of the bladder. Acute infection presents with Katayama fever. Diagnosis is based on detecting eggs in urine or stool, as well as serological tests. Treatment includes praziquantel, often supplemented with corticosteroids. Prevention involves avoiding contact with contaminated water. Untreated schistosomiasis can lead to serious complications, including bladder cancer. Material and methods: Literature available in the PubMed database was reviewed using the following keywords: schistosomiasis; bladder cancer; Schistosoma haematobium; bilharzia; blood fluke. Summary Schistosomiasis induces bladder cancer as a result of the chronic inflammatory condition in the urinary tract. The dominant histological type is SCC. Bladder cancer resulting from schistosomiasis is characterized by a younger age of onset and more advanced clinical stages. In the case of bilharzia detection, eradication of the parasite is recommended to prevent the development of cancer.